2019
DOI: 10.7717/peerj.7054
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and tissue-specific expression of odorant-binding proteins and chemosensory proteins in adults of the scarab beetle Hylamorpha elegans (Burmeister) (Coleoptera: Scarabaeidae)

Abstract: In this study, we addressed the sex- and tissue-specific expression patterns of odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) in Hylamorpha elegans (Burmeister), an important native scarab beetle pest species from Chile. Similar to other members of its family, this scarab beetle exhibit habits that make difficult to control the pest by conventional methods. Hence, alternative ways to manage the pest populations based on chemical communication and signaling (such as disrupting mating or host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…The number of OBPs in D. rybakowi was lower than previously reported, but eleven OBPs were found in Podabrus annulatus, which was the same as in previous reports [54]. Furthermore, upon comparing CSP numbers in D. rybakowi with those in other Coleoptera species, there were differences in twelve CSP genes in H. axyridis and C. bowringi, respectively [11,12], but similar CSP genes were found in Hylamorpha elegans (four CSPs), A. eugenii (six CSPs) [14], and C. maculatus (seven CSPs) [13,55]. The differences in the number of OBPs and CSPs may be due to the variation in the chemical environment of different species, where these species have evolved for a long time [56].…”
Section: Antennal Transcriptome Analysissupporting
confidence: 86%
“…The number of OBPs in D. rybakowi was lower than previously reported, but eleven OBPs were found in Podabrus annulatus, which was the same as in previous reports [54]. Furthermore, upon comparing CSP numbers in D. rybakowi with those in other Coleoptera species, there were differences in twelve CSP genes in H. axyridis and C. bowringi, respectively [11,12], but similar CSP genes were found in Hylamorpha elegans (four CSPs), A. eugenii (six CSPs) [14], and C. maculatus (seven CSPs) [13,55]. The differences in the number of OBPs and CSPs may be due to the variation in the chemical environment of different species, where these species have evolved for a long time [56].…”
Section: Antennal Transcriptome Analysissupporting
confidence: 86%
“…Also, among other Pleurosticts (i.e., the paraphyletic "Melolonthinae", Cetoniinae, and Rutelinae), there are some quite speciespoor lineages and slowly diverging lineages with "modern" sensilla (Table 1). Hence, we see the here presented hypotheses and results as a starting point to refine our phylogenetical understanding of the Scarabaeoidea but most of all to open up for a molecular characterization of antennal sensilla functionality, regarding pheromones and odor binding proteins of sensilla (e.g., Leal 2001;Nikonov et al 2002;González-González et al 2019) to improve our understanding of their chemical communication, ecology and evolution.…”
Section: Discussionmentioning
confidence: 92%
“…Li et al found that PrapCSP20 was enriched in the testes of Pieris rapae and probably participated in the reproduction of insects [42]. A variety of CSPs were found in insects such as Hylamorpha elegans (HeleCSP3) [50], Ophraella ommuna Lesage (Ocom-CSP12) [51], and Scopula subpunctaria Herrich-Schaeffer (SubCSP1/16) [52] that may be involved in insect egg-laying behavior. Therefore, we cannot exclude that SnitCSP2 plays other roles in S. nitobei.…”
Section: Discussionmentioning
confidence: 99%